The interplay between tissue growth and scaffold degradation in engineered tissue constructs - O'Dea, Reuben D.; Osborne, J.M.; El Haj, A.; Byrne, H.M.; Waters, S.L. (Springer, 2013)
In vitro tissue engineering is emerging as a potential tool to meet the high demand for replacement tissue, caused by the increased incidence of tissue degeneration and damage. A key challenge in this field is ensuring that the mechanical properties of the engineered tissue are appropriate for the in vivo environment. Achieving this goal will require detailed understanding of the interplay between cell proliferation, extracellular matrix (ECM) deposition and scaffold degradation.